Bikunin loss in urine as useful marker for bladder carcinoma - Tsui, Ke-Hung; Tang, Petrus; Lin, Chiao-Yun; Chang, Phei-Lang; Chang, Chih-Hao; Yung, Benjamin Yat-Ming (The Journal of urology, 2010)
We searched for bladder tumor markers by analyzing urine samples from patients with bladder cancer and normal individuals. Proteins in urine samples of patients with cancer and normal subjects were systematically examined by 2-dimensional electrophoresis combined with matrix assisted laser desorption ionization time-of-flight mass spectrometry. Of the proteins bikunin expression was confirmed by Western blot analysis and further evaluated. To correlate urinary bikunin levels with clinical significance we examined urine samples from patients with bladder cancer and normal controls for bikunin expression in parallel with pro-urolinase-plasminogen activator, which was previously shown to be associated with advanced bladder carcinoma. A significant relationship was established between the low level and absence of bikunin, and pro-urolinase-plasminogen activator in urine samples from patients with bladder tumors. Analysis of urinary proteomes may be a feasible, noninvasive and efficient strategy for searching for potential bladder tumor biomarkers. We identified bikunin loss in urine as a potential bladder carcinoma marker.